Zanzibar Was a Country: Exile and Citizenship between East Africa and the Gulf - Mathews, Nathaniel (University of California Press, 2024)
Zanzibar Was a Country traces the history of a Swahili-speaking Arab diaspora from East Africa to Oman. In Oman today, whole communities in Muscat speak Swahili, have recent East African roots, and practice forms of sociality associated with the urban culture of the Swahili coast. These "Omani Zanzibaris" offer the most significant contemporary example in the Gulf, as well as in the wider Indian Ocean region, of an Afro-Arab community that maintains a living connection to Africa in a diasporic setting. While they come from all over East Africa, a large number are postrevolution exiles and emigrés from Zanzibar. Their stories provide a framework for the broader transregional entanglements of decolonization in Africa and the Arabian Gulf. Using both vernacular historiography and life histories of men and women from the community, Nathaniel Mathews argues that the traumatic memories of the Zanzibar Revolution of 1964 are important to nation-building on both sides of the Indian Ocean.
Keywords: Emigration -- Zanzibar -- Oman; Vie politique -- Zanzibar -- 1963-1964; Vie politique -- Zanzibar -- 1964-1985

De Zanzibar à Oman, la douloureuse mémoire des exilés - Müller, Quentin (Orient XXI, 2019)
Quand l’empire maritime omanais s’étendait du sud de l’Iran au nord du Mozambique, l’île africaine de Zanzibar était au cœur du commerce d’esclaves. En 1964, une (...)
Keywords: Emigration -- Zanzibar -- Oman

“To Everyone Who Told Zanzis That They Are Not Omani”: Young Swahili-speaking Omanis’ Belonging in Postdiaspora Oman - Fay, Franziska (Arabian Humanities, 2022)
In this article, I explore some of the contemporary forms of expression that young Swahili-speakers below the age of 35 turn to in Oman to make claims to Omani citizenship and belonging. Building on long-standing discussions of Zanzibari-Omani identity, I discuss how second and third generation Zanzibari-Omanis of mixed backgrounds negotiate a sense of being both ‘Swahili’ and ‘Arab’ as part of their broader understandings of what it means to be Omani. I propose that foregrounding young Swahili-speaking Omani people’s modes of blending belongings can contribute to conversations on what it means to be ‘young’, ‘Omani’, ‘Swahili-speaking’ and a second or third generation postdiasporan. The article builds on exploratory fieldwork conducted in Oman in 2018 and 2019. It examines young people’s creative expressions through digital social media and against the backdrop of the Oman Vision 2040. These additional sources shed further light on some of the meanings of being a young Swahili-speaker in present-day Oman.
Keywords: Emigration -- Zanzibar -- Oman

The ethnic label Zinjibari: Politics and language choice implications among Swahili speakers in Oman - Kharusi, Nafla S. (Ethnicities, 2012)
The ethnic label Zinjibari in Omani society has various connotations that depend on who is using the term and about whom it is being used. Through participant observation and within the context of ethnolinguistic identity theory, this qualitative study aims to demonstrate how the label Zinjibari can function as an outgroup or ingroup label, as a mark of solidarity, as a term of prestige or as a slur. It is also proposed that these different connotations influence language choice among Oman’s Swahili speakers.
Keywords: Emigration -- Zanzibar -- Oman